Mindfulness as an Intervention for Recalling Information from a Lecture as a Measure of Academic Performance in Higher Education: A Randomized Experiment. (January 2018) - Bennett, Rebecca Iranzo; Egan, Helen; Cook, Amy; Mantzios, Michail
Higher education students experience heightened levels of stress and anxiety, and report experiencing negative thoughts and emotions, which influence information retention and recall. In a randomized experiment, we assigned participants to either a mindfulness meditation or an audiobook listening condition, and recorded the information recalled from a previously attended lecture, which was controlled for in subsequent analyses for trait resiliency and trait mindfulness. Participants placed in the mindfulness meditation condition recalled significantly more information than participants who were placed in the audiobook listening condition, even when controlling for resiliency and mindfulness. Future directions are suggested in an attempt to expand the literature and research around higher education, mindfulness and individual differences.